THE NATIONAL RURAL DEVELOPMENT PROGRAM - A CHANCE FOR AGROTOURISM DEVELOPMENT IN THE SUCEAVA COUNTY - Roxana FRANZUTTI; Cătălin Răzvan VÎNTU; Dragoș SMEDESCU; Dănuț UNGUREANU; Valentina Constanța TUDOR; Gina FîNTîNERU (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Since the 1950's, the tourism industry played a very important role for the global economic development. In 2017, tourism contributed with a fare of around 10% at the worldwide level. For the European Union, tourism has a very high significance for the market. Half of the tourist international arrivals are taken over by the European region and the economic contribution is similar for the rest of the world. Beside this, tourism has a high relevance for employment, with a contribution of around 12%. Unfortunately, for Romania, a country with a very high tourism potential, its resources are not exploited as appropriate, and the tourism contribution represents half of the European average. Our country occupies the 159th position out of 185. Besides this, the agrotourism for the Romanian market does not have a very high share, as it is still a developing segment of tourism. It started to take amplitude from 2000, when Romania received accession funds through the SAPARD support program. Since 2007, agrotourism received financing through the National Rural Development Program (NRDP) in the two multi annual financial frameworks: 2007-2013 and 2014-2020. The present study aims to analyse the situation in the N-E region and Suceava County from an agrotourism perspective by taking into consideration the effect of the rural development program on the number of agrotouristic structures, number of beds and employment. By the number of agrotouristic structures, the county occupies the third place in Romania, passed by Harghita County (281) and Brasov County (200) in 2007.